Clinic and treatment of bronchial asthma, combined with cardiovascularpathology - N. V. Gordeyeva; I. V. Demko; M. M. Petrova; I. P. Artyukhov (Бюллетень сибирской медицины)
The purpose of research - to study cardiovascular diseases frequency in patients with bronchial asthma (BA), the influence of cardiovascular disease on clinical course and severity of BA, the role of base and symptomatic therapy, to evaluate quality of diagnostics and treatment of cardiovascular disease in patients with BA. The date of patients register BA in Krasnoyarsk (2005) was analyzed - 5 104 patients. The frequency of occurrence of BA with cardiovascular pathology is high and amounts to 88,3%. Small number of patients with severity course of BA - 55%, middle severity stage - 44%, invalidity - 64%. It was revealed, that cardiovascular pathology appears against a background BA. The part of patients with cardial pathology before BA diagnostics had therapy, influenced on hyperactivity and this therapy assisted in forming and worsening of asthma. Base therapy of BA in most cases did not correspond to severity stage of asthma and recommendations of GINA. The absences of symptom control is bound up with unregular research functional lung ability and with insufficient attention to diagnostics and treatment accompanied pathology of cardiovascular organs. Not only adequate therapy but study of patients with the purpose of complex realization of recommendation, decrees of risk factors and treatment of accompanied pathology is necessary for improvement of asthma control, decrease of exacerbation number, unplanned visits of doctor and calls to emergency.